Upregulation of tRNA-Ser-AGA-2-1 Promotes Malignant Behavior in Normal Bronchial Cells - Santos, Mafalda; Fidalgo, Ana; Varanda, Ana Sofia; Soares, Ana Raquel; Almeida, Gabriela M.; Martins, Diana; Mendes, Nuno; Oliveira, Carla; Santos, Manuel A. S. (Frontiers in Molecular Biosciences, 2022)
Serine tRNAs (tRNASer) are frequently overexpressed in tumors and associated with poor prognosis and increased risk of recurrence in breast cancer. Impairment of tRNA biogenesis and abundance also impacts proteome homeostasis, and activates protein quality control systems. Herein, we aimed at testing whether increasing tRNASer abundance could foster tumor establishment through activation of the UPR. In order to do so, firstly we confirmed that the expression of tRNA-Ser-AGA-2-1 (hereafter tRNASer(AGA)) was is upregulated by 1.79-fold in Stage I NSCLC tumors when compared to normal tissue. To study the impact of tRNASer(AGA) in early stage tumorigenesis, we induced its upregulation in a non-tumoral bronchial cell line, BEAS-2B. Upregulation of this tRNA increased cellular proliferation and protein synthesis rate, driven by eIF2α dephosphorylation and ATF4 activation downstream of PERK signaling. Futhermore, tRNASer(AGA) enhanced transformation potential in vitro, and promoted the establishment of slow growing tumors with aggressive features in nude mice. Our work highlights the importance of studying tRNA deregulation on early stage tumorigenesis, as they may be potential malignancy and aggressiveness biomarkers.